The Manhattan Project at Oak Ridge - Welsh, Teresa S. (Qualitative and Quantitative Methods in Libraries, 2019)
The photographs of Ed Westcott, a civilian hired to document the Manhattan Project at Oak Ridge, Tennessee, are a valuable educational resource for school children as well as scholars. During the war years, Westcott was the official government documentarian of the construction and operation of Oak Ridge as well as photojournalist for the local newspaper. His photographs, which are a cultural and historical record of that unique time and place, have been published in numerous books on the history of the Manhattan Project. This study is based on historical documentation as well as a lecture by and interviews with Westcott.